Pneumo-Scrotum as Diagnosis of Ectopic Air in Other Locations - López Escobar, Alejandro; Lorén Martín, Jennifer; Jimeno Ruiz, Sara (My University, 2024)
A 43-year-old woman presented spontaneous delivery at 35+4 weeks. An unreactive fetus was born in addition to abruptio placentae, joint exit of placenta and fetus and a true cord knot. We proceed to a deep resuscitation. During the ventilation it was observed that the scrotal volume was increased. A X-ray was done confirming ectopic air in chest, peritoneum and scrotum. Pneumo-scrotum is a rare disease that has been described in immature newborns. It has been reported secondary as infection, after aggressive resuscitation, as a consequence of mechanical ventilation and secondary to gastric perforations. Its treatment is etiological. The simple thoracic and abdominal radiography are sufficient for diagnosis. In the neonatal period, the presence of pneumo-scrotum during resuscitation may reveal ectopic air in the thorax or peritoneum. Keywords: Pneumo-scrotum, ectopic-air, resuscitation.
Keywords: Pneumo-scrotum, ectopic-air, resuscitation.